2022
DOI: 10.1038/s41598-022-15782-7
|View full text |Cite|
|
Sign up to set email alerts
|

Mode of action of fluopyram in plant-parasitic nematodes

Abstract: Plant-parasitic nematodes (PPN) are responsible for severe yield losses in crop production. Management is challenging as effective and safe means are rare. Recently, it has been discovered that the succinate dehydrogenase (SDH) inhibitor fluopyram is highly effective against PPN while accompanying an excellent safety profile. Here we show that fluopyram is a potent inhibitor of SDH in nematodes but not in mammals, insects and earthworm, explaining the selectivity on molecular level. As a consequence of SDH inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The relative amounts of ATP, adenosine diphosphate (ADP), and adenosine monophosphate (AMP) in organisms reveal the potential effects of pesticides on energy metabolism. Therefore, an adenylate energy charge (AEC) assay was performed to illustrate ATP biosynthesis according to the method described by Schleker et al 31 Nematodes were treated with the flu nanoagent (20 mg/L) or flu for 48 h, washed with PBS, and collected. Nucleotides were extracted and used to examine ATP biosynthesis using an ATP, ADP, AMP Content High-Performance Liquid Chromatography (HPLC) Assay Kit (Solarbio Science & Technology Co., Ltd).…”
Section: Particle Size Measurement and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The relative amounts of ATP, adenosine diphosphate (ADP), and adenosine monophosphate (AMP) in organisms reveal the potential effects of pesticides on energy metabolism. Therefore, an adenylate energy charge (AEC) assay was performed to illustrate ATP biosynthesis according to the method described by Schleker et al 31 Nematodes were treated with the flu nanoagent (20 mg/L) or flu for 48 h, washed with PBS, and collected. Nucleotides were extracted and used to examine ATP biosynthesis using an ATP, ADP, AMP Content High-Performance Liquid Chromatography (HPLC) Assay Kit (Solarbio Science & Technology Co., Ltd).…”
Section: Particle Size Measurement and Morphologymentioning
confidence: 99%
“…Flu is a highly selective SDH inhibitor of nematodes and fungal pathogens that does not affect the activity of mammals, insects, or earthworms' SDH. 31 A recent publication reported that SDH activity was significantly reduced in nematodes treated with flu. 30 As shown in Figure 5B, SDH inhibition was consistently higher in flu nanoagent-exposed nematodes compared to flu alone at all tested concentrations, and the pIC 50 value was increased from 8.81 to 11.04 with the aid of SPc, revealing that SDH activity was further inhibited by SPc-delivered flu.…”
Section: Amplified Adverse Impacts Of Flu Nanoagents On Oxidative Str...mentioning
confidence: 99%
“…This fungicide acts by inhibiting the succinate dehydrogenase enzyme in complex II of the electron transport chain of mitochondria. 1,2 Although the fluopyram molecule is already well known in several countries in Europe, the United States and also Australia, this compound was only authorized for marketing and use in Brazil in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Fluopyram and pydiflumetofen, introduced in the last decade, are systemic succinate dehydrogenase inhibitors (SDHI) fungicides, protecting soybean seedlings against soil-borne diseases, including SCN and other plant-parasitic nematodes. Similar to fungi, the succinate dehydrogenase (SDH) complex is also the target for fluopyram and pydiflumetofen in plant-parasitic nematodes ( Heiken, 2017 ; Schleker et al., 2022 ). In the mitochondrial matrix, SDH catalyzes the oxidation of succinate to fumarate, transferring electrons to ubiquinone without pumping protons across the mitochondrial inner membrane ( Huang and Millar, 2013 ).…”
Section: Introductionmentioning
confidence: 99%